If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = 4f(-5) + -7 Multiply g * x gx = 4f(-5) + -7 Reorder the terms for easier multiplication: gx = 4 * -5f + -7 Multiply 4 * -5 gx = -20f + -7 Reorder the terms: gx = -7 + -20f Solving gx = -7 + -20f Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = -7x-1 + -20fx-1 Simplifying g = -7x-1 + -20fx-1 Reorder the terms: g = -20fx-1 + -7x-1
| 4x+9=3(x+10)+8 | | x/-16=8 | | 4x+9=(x+10)+8 | | 3x^2-120x-3600=0 | | [180(n-2)]/n=165 | | -9x+2x-3x=0 | | 6x-14=45 | | x(2+10)= | | 2*x+10*x= | | 5x-11x=48 | | 532/14 | | -0.4x=40 | | 490/14 | | 168=10x+18 | | -5x^2-10z=0 | | B(x)=35.00-0.08x | | -3/7m=-9 | | Y/19=-10 | | 25+86=6x | | (M+x)(n-m)=1 | | 11-2i/8i | | 6(u-4)=2u-40 | | 2(3n+4)=54+6n | | 4x-4/×-7 | | M(n-m)+x(n-m)=1 | | 4v+28=-4(v-9) | | 180-(90-3x)=x-20 | | X^2+y^2-6x+4y+9=0 | | 7*z^2-2.25z+z=0 | | -3x^2-14x=0 | | x-38=50 | | 6(y+4)=-7y-41 |